Marketing Assistance for Home Industry Products Based on Social Media - Puspitasari, Riska; Nuri , Desi Rahma; Ningsih, Kartika Wahyu (Zabags International Journal of Engagement, 2024)
This assistance is carried out to help the community, especially home industry players, know the benefits of using social media in developing marketing of products produced by home industries in Muara Sabak Barat sub-district. The subjects in this research were selected using purposive sampling involving 12 home industry players. The result of this assistance is that home industry players have innovation skills in marketing products through social media market place Facebook, Instagram, and via WhatsApp business which is currently trending and much loved by the Indonesian people in general and the people of Muara Sabak Barat sub-district in particular. Some of these social media are media with the most active users which are used as a means of utilizing promotional media for home industry products that use social media. Social media is the right tool that can be used as an effective communication medium to respond to consumers and increase market share as well as monitor the sales volume of the product